(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The Covid-19 pandemic outbreak is very detrimental to the community in the health sector, they are limited in visiting health services, there is fear and anxiety of the community to contract the Covid-19 virus. This can lead to disrupted monitoring of the growth and development of children under five in health facilities. Child development is an important thing to pay attention to because child development in the early phase will affect child development in the next phase, around 7.6 million children worldwide die before reaching the age of 5 years and more than 190 million children who live cannot reach their potential development age. The Stimulation Detection and Early Intervention of Growth and Development (SDIDTK) program is one of the main programs of the Puskesmas. The purpose of this counseling is to increase the knowledge and understanding of parents, especially mothers, regarding early detection of growth and development problems in toddlers aged 2-6 years. Health education is carried out by face-to-face method by providing counseling using leaflets, with parents who have toddlers as participants. Measurement of knowladge can be done by giving a questionnaire measuring instrument in the form of pretest and posttest. The results of health counseling activities obtained by 30 respondents showed that at the time of the pretest as many as 13 respondents (43.33%) were in the good category and as many as 17 respondents (56.67%) were in the poor category. The conclusion in the implementation of health education regarding early detection of child growth and development monitoring has an impact on increasing knowledge and understanding in parents.